Navigating the Curricular Maze: Examining the Complexities of Articulated Pathways for Transfer Students in Engineering. Issue 11 (2nd November 2021) - Grote, Dustin Michael; Knight, David B.; Lee, Walter C.; Watford, Bevlee A.
ABSTRACT: States and institutions employ articulation agreements to streamline curricular pathways. We investigate the efficacy of that streamlining by considering how course sequences, enacted through pre- and co-requisites, relate to graduation rates for transfer students at different time intervals. Applying a curricular complexity framework that quantifies the complexities of curriculum pathways, we compared the curricular complexities of transfer and first-time-in-college (FTIC) pathways in engineering and correlate those complexity scores with graduation rates at different time intervals. The institutions examined in this study include a mid-Atlantic research university and four of its largest feeder community colleges geographically distributed across the state. We found that, in aggregate, transfer student pathways are less complex than FTIC pathways, although complexity metrics vary across engineering disciplines and sending institutions. Although curricular complexity correlates with graduation rates for FTIC students at different time intervals, the same relationship does not hold for transfer students. The curricular complexity metric is useful for understanding the complexity FTIC students encounter in engineering and correlates with their graduation rates at different time intervals. However, the tool falls short of capturing some nuances of curricular complexity for transfer students. We suggest ways to enhance the metric to depict complexities in curriculum for transfer students.